Affiliate marketing business model education in promoting keloria products - Ahmad Afandi; Syahrul Amsari; Isra Hayati; Syahrani Devi; Fachrul Rozi Lubis (Community Empowerment, 2022)
The era of the industrial revolution 4.0 and globalization made major changes in various fields, one of which is technology. One of the digital marketing strategies is affiliate marketing, which allows someone to market other people's products simply by spreading promotional links. In this activity, the team held seminars and training on affiliate marketing business models in marketing keloria products which aimed to increase participants' knowledge of digital marketing and affiliate marketing and encourage participants to join as affiliate partners of PT. Keloria Moringa Jaya. This seminar and training was carried out in 3 stages, namely preparation, seminar and training, and evaluation. The evaluation results show the participants' satisfaction with the training material and design presented. In addition, this activity succeeded in increasing participants' knowledge about digital marketing, especially social media marketing and affiliate marketing-based marketing models.